Floating Knee Injury Associated with Patellar Tendon Rupture: A Case Report and Review of Literature - Singaravadivelu Vaidyanathan; Jagannath Panchanathan Ganesan; Mugundhan Moongilpatti Sengodan (Case Reports in Orthopedics)
Floating knee injuries are frequently associated with other concomitant injuries to the ipsilateral limb or other parts of body of which injury to the ipsilateral knee ligaments carries significance for various reasons. A middle-aged man sustained a floating knee injury following RTA. DCS fixation by bridge plating technique for the distal femur and lateral buttress plating by MIPO technique for proximal tibia were planned and executed under spinal anesthesia with image intensifier. In addition, there were patellar tendon rupture along with avulsion of VMO from the medial border of patella and torn MPFL, which we have missed initially. To the best of our knowledge no similar case has been reported in English literature so far. We have reviewed the literature and proposed a different interpretation of Blake and McBride classification.